Development and tribo-mechanical properties of functional ternary nitride coatings: Applications-based comprehensive review. (January 2021) - Ghufran, Muhammad; Uddin, Ghulam Moeen; Arafat, Syed Muhammad; Jawad, Muhammad; Rehman, Abdul
Friction and wear are very crucial aspects of the performance, service life, and the operational costs for a mechanical component or equipment. To reduce the friction and wear at the interface of the sliding or mating parts, different conventional binary coatings like TiN, CrN, TiC, etc., have been used in the last two decades. But ternary nitride coatings have replaced the binary coatings due to better tribo-mechanical properties. Now, ternary nitride coatings are being extensively used in several fields such as cutting tools, machinery parts, orthopedic implants, microelectronics, marine equipment, decorative purposes, automotive, aerospace industry, etc. Many researchers have developed and investigated the ternary nitride coatings for different applications. Nonetheless, there is a huge research potential in the development and optimization of the tribo-mechanical properties of the ternary nitride coatings. Therefore, tribo-mechanical studies of the ternary nitride coatings are needed for fostering the new industrial applications. This paper is focused to summarize and compare the tribo-mechanical properties of the ternary nitride coatings comprehensively and aims to explore the novel research directions in the development of the ternary nitride coatings.